Español - Español, Español; Español, Español; Español, Español; Español, Español (Ars Pharmaceutica (Internet), 1985)
At the present paper we have studied the relationship between the composition of the calculi and that of the water in different place s of the Granada Province. We have obtained sorne conclusions with the only objection of the scarce amounts of the lithiasic patients studied.